Diffusion of Mobile Health Apps Among Smartphone Users : Role of Neighborhood Effects, Informational Network Effects, and Social Ties in Health 3.0 - Kesharwani, Ankit; Roy, Souvik (Indian Journal of Marketing, 2017)
The convergence of mobile technology with an evolving healthcare delivery system has ushered a wave of disruptive innovations that has bought a paradigm shift in healthcare delivery services; known as Health 3.0. If Health 1.0 was about content (portals, sites like WebMD), and Health 2.0 was focused around communities that capitalize on the knowledgeÂ gained by specific patients and their physicians (a diabetes message board), then Health 3.0 is about coherence of health information and active participation from users itself. Digital natives (DNs) are users born after 1980, grown up with digital devices and who are developing N-fluence networks (Topscott, 2008) via the Internet, especially through social media. This study proposed a conceptual model that deals with the diffusion of mobile health apps (mHealth apps) among digital natives (consumer reviews) and the role played by neighborhood effects, social network effects, and opinion leadership in such diffusion.